Distinguishability notion based on Wootters statistical distance : application to discrete maps - Gómez, Ignacio Sebastián (2017)
Fil: Gómez, Ignacio Sebastián. Universidad Nacional de La Plata. Instituto de Física La Plata; Argentina.